Representativeness, Complementarity, and Degree of Local Extirpation Risk for Thamnophis Species Inside and Outside of Protected Areas of Mexico - Crystian Sadiel Venegas-Barrera; Javier Manjarrez; Ángel Rodríguez-Moreno; Yeimi Alexandra Mendoza-Walle; Jorge Víctor Horta-Vega; Itzel R. Rodríguez-deLeón; Armando Sunny; Ausencio Azuara Domínguez (Ecologies)
Protected areas (PAs) are geographical spaces intended to conserve populations, communities, and ecosystems, in which species richness must be maximized, the conserved area must be minimized, and anthropogenic pressure must be reduced. The present study analyzed the representativeness, complementarity, and degree of risk of 25 garter snake species of the genus Thamnophis in the PAs of Mexico. This study proposes that at least 17% of the potential geographic distribution (PGD) of species will be found inside PAs and in areas (Aichi Target 11) with a low human footprint (HF). The PGD of species was associated with the PAs and HF layers to identify where and which species could be at local extirpation risk by human activities. The results indicate that the federal PAs contain 85.2% of the species, while the state PAs contain 77.7% of the species. An average of 13.4% of the PGD of these species is found inside PAs, and two species are found outside. In 13 federal PAs and 10 state PAs, the Thamnophis species present high local extirpation risk from human activities. In total, 37% of species are found in PAs with a medium to very high human footprint; therefore, their persistence could be at local extirpation risk. Compared to other taxa, species of the genus Thamnophis are well represented. However, the PDG of more than half of the species achieves Aichi Target 11.